Two new species of Sciophila Meigen (Diptera: Mycetophilidae) from Turkey, with a key to the Western Palaearctic species of the S. lutea Macquart group - Bechev, Dimitar; Koç, Hasan (Zootaxa, 2006)
Two new species, Sciophila muglolutea sp. n. and S. turkolutea sp. n., from southeastern Turkey are described and illustrated. The second record of S. delphis Chandler, previously known only from the holotype, is reported. A key to the Western Palaearctic species of the S. lutea Macquart group is provided, and data on the distribution of the Palaearctic species are presented.